2017
DOI: 10.22521/unibulletin.2017.61.8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Literacy Dimensions of Pre-Service Teachers

Abstract: In this research, it is aimed to determine pre-service science teachers' environment attitude, behavior and perceptions in terms of different variables. In this research, the relational screening model method was used. The study group consists of 265 preservice science teachers from a state university in Turkey. The research was conducted during the fall semester of 2015-2016. In this research, the Environment Attitude Scale (EAS), Environment Behavior Scale (EBS), and Environment Perceptions Scale (EPS) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The results showed that the environmental background of pre-service teachers was positively related to their environmental literacy and attitudes as well as gender. However, another study in Turkey by Karakaya, Avgin and Yilmaz (2017) found no significant difference in pre-service teachers' environmental attitude, behavior and perceptions in terms of gender and longest-lived place. Nevertheless, the study reported a statistically significant difference in the three environmental domains in respect of student-teachers' exposure to environmental education lessons, academic field and grade level.…”
Section: Literature Reviewmentioning
confidence: 88%
“…The results showed that the environmental background of pre-service teachers was positively related to their environmental literacy and attitudes as well as gender. However, another study in Turkey by Karakaya, Avgin and Yilmaz (2017) found no significant difference in pre-service teachers' environmental attitude, behavior and perceptions in terms of gender and longest-lived place. Nevertheless, the study reported a statistically significant difference in the three environmental domains in respect of student-teachers' exposure to environmental education lessons, academic field and grade level.…”
Section: Literature Reviewmentioning
confidence: 88%
“…In terms of environmental behaviours, it is understood that females are more environmentally friendly in their physical protection behaviour and individual and social persuasion behaviours. Although there are studies concluding that gender is not effective in terms of environmental behaviour (Erbasan & Erkol, 2020;Karakaya, Avgın & Yılmaz, 2018;Karakaya, Avgın & Yılmaz, 2018;Karakuş & Çimen, 2020Karakuş & Çimen, Özdemir, 2012Sungur, 2017), they indicate that females have a more friendly approach to the environment than males (Fernandez Manzanal, Rodriguez-Barreiro and Carrasquer, 2007;Güriçin, Sevinç, 2020;Karakaya and Yılmaz, 2017;Keleş and Özer, 2020;Plavsic, 2013;Sönmez, 2020;Sönmez, 2019;Zelezny, Chua and Aldrich, 2000). Ecofeminist literature suggests that females relate to the environment at a more empathetic level and there are gender differences in human relationships (Bloodhart & Swim, 2010;Stephens, Jacobson, & King, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…When the studies in literature examined, it was seen that, in general, case studies were conducted with different groups only in the context of environmental ethics (Bozdemir & Faiz, 2018;Cappellaro, 2016;Çobanoğlu, Karakaya, & Türer, 2012;Erten, 2007;Karakaya, 2009;Erten & Aydoğdu, 2011;Kortenkamp & Moore, 2001;Thompson & Barton, 1994;Thompson, 1998;Özdemir, 2014;) or only in the context of environmental behaviour (Özgen (2012) and Öcal (2013) Silkü (2011) Pe'er, Goldman and Yavetz (2007Hsu (2004)). In addition, there are studies on whether environmental ethics or environmental behaviour change according to variables such as gender [ (Şama, 2003;Çabuk & Karacaoğlu, 2003;Deniş & Genç, 2007;Manzaral, Barreiro, & Carrasquer, 2007;Erten, 2008;Kahyaoğlu, Daban, & Yangın, 2008;Karakaya, 2009;Şenyurt, Temel, & Özkahraman, 2011;Wongchantra & Nuangchalerm, 2011;Çobanoğlu, Karakaya, & Türer, 2012;Kiper, Korkut, & Üstün Topal, 2017;Karakaya & Yılmaz, 2017;Akyol (2014) Genç & Genç (2013De Lavega (2004)] department [ (Şama, 2003;Çabuk & Karacaoğlu, 2003;Kahyaoğlu, Daban, & Yangın, 2008;Karakaya, 2009;Saka, Sürmeli, & Öztuna, 2009;Şenyurt, Temel, & Özkahraman, 2011;Can, 2012;Kiper, Korkut, & Üstün Topal, 2017)], and class leveandl (Çabuk & Karacaoğlu, 2003;…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Karakaya, Avgin and Yilmaz conclude that focused environmental education programmes could positively influence EB. 72 Figure 3 contrasts the self-reported behaviour of participants who had completed an environmental course with those who had not. The F-test assessed the hypothesis that behaviour was the same, regardless of attendance of environmental courses.…”
Section: Meb According To the Environmental Course Determinant (2017 mentioning
confidence: 99%